The first licensed dengue vaccine: can it be used in travelers? - Wilder-Smith, Annelies (Current opinion in infectious diseases, 2019)
Purpose of review: The first dengue vaccine (Dengvaxia) was endorsed by the European Medicine Agency and the US Food and Drug Administration. Given the excess risk of severe dengue in seronegative vaccinees, use is restricted to seropositive individuals. Dengvaxia confers high protection against severe dengue in seropositive vaccinees. - Recent findings: With increasing global travel, the probability of travelers being seropositive increases. Such seropositive travelers may be at increased risk of severe dengue as a result of a second dengue infection during repeat travel. Nevertheless, the use of Dengvaxia in travelers requires a careful analysis of all the factors. Seropositive travelers only present a minority of all travelers. A validated rapid diagnostic test to screen for dengue serostatus is not yet available. Such a test should be highly specific to avoid inadvertent vaccination of seronegative individuals. The three-dose regimen precludes the use in most travelers who tend to present at travel clinics less than 6 weeks prior to departure. Furthermore, questions about potential sub-optimal immunogenicity in seropositives in nonendemic settings, and the need and timing of boosters remain unanswered. - Summary: Although there could potentially be substantial protection against severe dengue in seropositive travelers, Dengvaxia is far from an ideal travel vaccine.
Gesehen am 17.02.2020